1983
DOI: 10.1017/s0021859600037825
|View full text |Cite
|
Sign up to set email alerts
|

Grain and fodder legumes as preceding crops affecting the yield and N economy of rice

Abstract: Experiments made for 2 years on a sandy-loam soil showed that previous grain crops of mung bean (Vigna radiata), cow pea (V. unguiculata) and black gram (V. mungo) increased the grain and straw yield of a subsequent crop of rice relative to previous fodder crops of maize or guar bean (Cyamopsis tetragonoloba) or a grain crop of Phaseolus bean (Phaseohcs vulgar is). The benefits from preceding crops of mung bean, cow pea or black gram were equivalent to 36-67 kg N/ha of chemical fertilizer applied to the rice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…2). Such increased cereal yields following legume crops were attributed to the N contribution from legumes in crop rotation (De et al, 1983;Kumar Rao et aI., 1983;Nambiar, 1990). This opinion is not held by all (Cook, 1988;Danso and Pappastylianou, 1992;Fyson and Oaks, 1990;Russelle el aI., 1987;Wani et aI., 19913, 19943).…”
Section: Beneficial Effects Of Legumesmentioning
confidence: 99%
“…2). Such increased cereal yields following legume crops were attributed to the N contribution from legumes in crop rotation (De et al, 1983;Kumar Rao et aI., 1983;Nambiar, 1990). This opinion is not held by all (Cook, 1988;Danso and Pappastylianou, 1992;Fyson and Oaks, 1990;Russelle el aI., 1987;Wani et aI., 19913, 19943).…”
Section: Beneficial Effects Of Legumesmentioning
confidence: 99%
“…Such increased cereal yields are usually attributed to enrichment of soil with nitrogen due to N2 fixation by legumes or their effect in conserving soil N resulting in increased N mineralization and increased proportion of active N fraction (Nambiar et al -1982;De et al 1983;Senararne and Hardarson 1988;Wani et al 1994). Evidence is increasing that legumes in a rotation are associated with more than just their N effect (Bezdicek and Granatstein 1989;Wani er al.…”
Section: Canadian Journal Of Soil Sc'ea/cementioning
confidence: 99%
“…The cow pea or green gram had similar residual effect on the succeeding pearl millet as they probably left identical qualities of nitrogen in the soil. De, Rao & Ali (1983), Doughton & Mackenzie (1984), De et al (1985) and Velayudham & Seth (1986) reported that cow pea and green gram contributed about 25-60 kg N/ha to the subsequent crop in crop rotations. Pearl millet yielded less when sown after maize than after fallow and legumes.…”
Section: Grain Yield Of Pearl Milletmentioning
confidence: 99%